Latina Youth, Education, and Citizenship: A Feminist Transnational Analysis. (2nd April 2016) - Bondy, Jennifer M.
Abstract: This article explores adolescent Latinas' citizenship identities in school from a feminist transnational perspective. Data were drawn from qualitative research studies on Latina youths' educational experiences and from a qualitative project conducted by the author. Cultural citizenship theories were used to analyze the data. The analysis revealed that adolescent Latinas experience their citizenship identities' being-made through two strategies: (i) stereotypical images and (ii) language ideologies. The analysis also revealed that Latina youth self-make their citizenship identities through three strategies: (i) embracing education, (ii) cultural practices, and (iii) new citizenship identities in transnational spaces. Analyses suggest the need for more transnational approaches in educational research and practice on citizenship education. A feminist transnational approach highlights how discourses and images on Latinas, Latina/o immigration, and citizens materialize in school and provide the conditions in which adolescent Latinas negotiate their citizenship identities.